Characterization of IFN-γ Detection and Electrochemical Proximity Assay by a Novel Multi-Parametric/Multimodal Spectroscopy Apparatus. (25th October 2017) - Zhou, Lang; Chin, Bryan A; Simonian, Aleksandr L.
Abstract : Functional interfaces play a vital role in biosensing, which requires proper allocation, orientation, conformation, activities and stability to achieve high affinity and stability of the biomolecules. However, the characterization of functional interfaces is still challenging. Here, simultaneous measurement of Surface Plasmon Resonance, fluorescence, and electrochemistry has been demonstrated by a novel Multi-Parametric/Multimodal Spectroscopy Apparatus (MPMS). Using this system, the assembly of various functional interfaces, including aptamer-based IFN-γ detection, and Electrochemical Proximity Assay were characterized. MPMS enables simultaneous confirmation of binding events both quantitatively (number of events) and kinetically (speed) through SPR, fluorescence and electrochemistry, thus enhancing the power of interface characterization sensing techniques.